Caribbean media directory - McPherson, Joseph, comp. (Jamaican Institute of Political Education KingstonJA, 1986)
Provides information regarding the existence of media publications and broadcasting units for twenty two Dutch, Spanish and English speaking Caribbean territories. Gives brief country profiles of each territory. Includes information on the frequency, publisher, circulation, price, address, and telephone number of each newspaper and gazette. States the type of ownership, hours of broadcast, address and telephone number for each radio or television station.